Pengaruh Dana Alokasi Umum (DAU), Pendapatan Asli Daerah (PAD), dan Dana Bagi Hasil (DBH) terhadap Belanja Modal dengan Sisa Lebih Pembiayaan Anggaran (SILPA) sebagai Variabel Pemoderasi pada Pemerintah Provinsi se-Indonesia Periode 2015-2019 - Syofyan Yuliantoni; Fefri Indra Arza (Universitas Negeri Padang, 2021)
This study aims to determine the effect of General Allocation Fund (DAU), Regional Original Income (PAD), and Revenue Sharing Fund (DBH) on Capital Expenditures with Excess Budget Financing (SILPA) as a Moderating Variable in Provincial Governments throughout Indonesia 2015-2019. The data use in this study is the report on the realization of APBD for the 2015-2019 fiscal year which is available on the DJPK website. The population and sample in this study ara all provincial governments in Indonesia consisting of 34 provinces from 2015-2019 with a total of 170 data. Hypothesis testing in this study uses the Moderated Regression Analysis (MRA) test. The result showed that DAU had a significant effect on capital spending, PAD and DBH had no effect on capital spending, SILPA does not moderate DAU, PAD, and DBH on capital expenditures.